Audit committee characteristics and quality of financial information: The role of the internal information environment and political connections - Omid Mehri Namakavarani; Abbas Ali Daryaei; Davood Askarany; Saeed Askary (Journal of Risk and Financial Management, 2021)
This study explores the relationship between audit committee characteristics and accounting information quality by justifying the role of the internal information environment and political connections under the theocracy state of Iran with syncretic politics. Using panel data of 558 firms from the Tehran Stock Exchange (TSE) for 2011-2016, we rank firms using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and entropy method for determination of the weight of evaluating indicators. The firms are positioned into high- to low-level political connections, and two proxies for audit committee characteristics are used: independence of audit committee and financial knowledge. Furthermore, three proxies are used for an internal information environment: earning announcement speed, the accuracy of earning forecasting and lack of financial restatements. Our findings show that there is a significant and positive relationship between the audit committee and financial information quality characteristics in high-level political connections, as well as between financial knowledge and financial information quality. Furthermore, the findings of this study suggest that the application of political economy theories could be appropriate for more inquiry.
Keywords: 330; accounting information quality; audit committee characteristics; internal information environment; political connections; TOPSIS